2017
DOI: 10.1002/da.22679
|View full text |Cite
|
Sign up to set email alerts
|

Proximal relationships between social support and PTSD symptom severity: A daily diary study of sexual assault survivors

Abstract: Background In cross‐sectional studies, social support and posttraumatic stress disorder (PTSD) symptoms appear related, in that higher severity of PTSD is associated with lower social support and vice versa. Theoretical models of the causal direction of this relationship differ. Most longitudinal studies suggest that PTSD symptoms erode social support over time, although some suggest that higher social support is prospectively associated with decrease in PTSD symptom severity. It is unclear, though, how social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 49 publications
3
38
0
1
Order By: Relevance
“…The moderated moderation model shows that, separately, sexual assault and exposure to the earthquake positively predict traumatic consequences, while social support predicts them negatively. Research has previously shown the efficacy of social support in dealing with traumatic consequences experienced by women (Bryant-Davis et al ., 2015; Ullman and Peter-Hagene, 2016; Dworkin et al ., 2018). Our results corroborate that social support plays a protective role in women, but go beyond that by also showing that it plays a protective role in cumulative trauma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The moderated moderation model shows that, separately, sexual assault and exposure to the earthquake positively predict traumatic consequences, while social support predicts them negatively. Research has previously shown the efficacy of social support in dealing with traumatic consequences experienced by women (Bryant-Davis et al ., 2015; Ullman and Peter-Hagene, 2016; Dworkin et al ., 2018). Our results corroborate that social support plays a protective role in women, but go beyond that by also showing that it plays a protective role in cumulative trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed that sexual assault is associated with multiple lifetime psychiatric disorders including PTSD, depression, anxiety, and others (Chen et al ., 2010). Studies conducted among sexually assaulted people in general, and among women particularly, have shown that they are more likely to present significant symptoms of PTSD, depression, anxiety, and substance use problems, among others (Ullman, 2016; Dworkin et al ., 2018; Scott et al ., 2018). These studies and others have also shown that social support is an important protective factor in helping women survivors of sexual assault cope with traumatic consequences (Bryant-Davis et al ., 2015; Ullman and Peter-Hagene, 2016; Dworkin et al ., 2018).…”
mentioning
confidence: 99%
“…Studies in military samples that tested both models support the social erosion model (King, Taft, King, Hammond, & Stone, 2006) or both models (Ren, Skinner, Lee, & Kazis, 1999;Shallcross, Arbisi, Polusny, Kramer, & Erbes, 2016;Woodward et al, 2018). Data from nonmilitary samples support social causation (Dworkin, Ullman, Stappenbeck, Brill, & Kaysen, 2018), social erosion (Nickerson et al, 2017), or both models (Platt, Lowe, Galea, Norris, & Koenen, 2016). Inconsistent findings may be due to heterogeneities in study design, such as duration of time since participants' trauma exposure, prevalence of PTSD in a given sample, and variability in assessment methods (Woodward et al, 2018).…”
Section: Contactmentioning
confidence: 89%
“…For instance, comparing a condition in which participants can have a phone call to a (supportive) loved one after a traumatic event, to a condition in which they are only allowed to talk to an (unsupportive) experimenter, and to a control condition in which they could not talk to any other person, could help to disentangle this effect. In addition, while people who generally have high social support tend to have lower PTSD symptoms on any given day, average PTSD symptom severity does not seem to be associated with day-to-day fluctuations in the availability of social support (Dworkin et al, 2018 ). For the present study, this would imply that the social support right after the MAST task may have not been enough to buffer memory coherence or state anxiety, and rather that we would need a follow-up design to create a larger difference between conditions (more social support over time in supportive group, less social support over time in unsupportive group), in order to be able to pick up differences in posttraumatic responses, like state anxiety or memory coherence.…”
Section: Discussionmentioning
confidence: 99%